UNDERSTAND THE CONCEPT OF BUSINESS COMMUNICATION THROUGH AI-BASED ELECTRONIC MEDIA FOR BUSINESS SUSTAINABILITY - Novika Ayu Triany; St Salmah Sharon; Monalisa (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2024)
This research aims to explore the application of artificial intelligence (AI) in business communication with a focus on the concepts of responsibility, monitoring, integrity and innovation (TMII). AI has significant potential to improve the efficiency and effectiveness of business communications, but its implementation requires a responsible and ethical approach. This research provides comprehensive guidance on managing AI-based business communications by considering aspects of responsibility, monitoring, integrity and innovation, to support business sustainability.